Manajemen Bandwidth Menggunakan Mikrotik dengan Mode Simple Queues pada Koperasi Bank KB Bukopin - Abdul Azis; Hendra Supendar; Riza Fahlapi (STIKes Ibnu Sina Ajibarang, 2023)
The slow speed of internet access is often a problem that most users of computer network services complain about because there are no restrictions or efficient bandwidth management. Bandwidth management is a concept in which several computers in an office or office environment can be connected to each other and share data and information in accessing the internet. In the application of bandwidth management with the simple queues method for optimizing computer network security systems on proxy routers, it is proven to be able to solve problems that are often complained of by most users of computer network services that are located in terms of availability, reliability, stability, performance stability and can provide protection to prevent unauthorized access or minimize attacks coming through the network against owned resources. It is often found that the process of accessing data communications and information for each user connected to the network feels slow, this is due to the existing bandwidth capacity being insufficient. Mikrotik is an operating system that is capable of turning a computer into a network router or often called a PC router. The operating system includes a full range of features for wireline and wireless, one of which is bandwidth management. With an upload bandwidth of 50 Mbps and a download of 50 Mbps, a bandwidth management of 2 Mbps, 5 Mbps, 10 Mbps and 15 Mbps.